Peningkatan Pengetahuan Remaja Mengenai Narkoba, Seks Bebas, dan HIV Menggunakan Kerangka Kerja Theory Of Planned Behavior - William Hadi Seputro; Mary Philia Elisabeth (Universitas Islam Tribakti Lirboyo Kediri, 2020)
The level of drug use and free sex behavior in Indonesia is still very high, as much as 28% and 32%, including in one area in a big city, after referred to as the BU area. Based on initial interviews with BU residents, adolescents in BU areas are predominantly drug users and perpetrators of free sex when they knew residents try to cover up and keep quiet. Starting from the desire of BU citizen to change, researchers conducted research using the Theory of Planned Behavior (TPB) framework to provide behavior change interventions for changes in BU residents. Research participants were members of the youth organization consisting of 15 people. Participants selected because they understand and share values ​​and culture with BU residents. Based on the results of the study, all of the participants who experienced changes had the intention to change. Increase in the cognitive realm, helping participants change internal who has an impact on behavior change. The behavior that initially pretended not to know turned into real action, such as listening to stories of unexposed adolescents so as not to be exposed to drugs and free sex and suggesting more positive activities.